CD68-positive tumor-associated macrophages predict unfavorable treatment outcomes in classical Hodgkin lymphoma in correlation with interim fluorodeoxyglucose-positron emission tomography assessment. Issue 2 (February 2015) - Touati, Mohamed; Delage-Corre, Manuela; Monteil, Jacques; Abraham, Julie; Moreau, Stéphane; Remenieras, Liliane; Gourin, Marie-Pierre; Dmytruk, Nataliya; Olivrie, Agnès; Turlure, Pascal; Girault, Stéphane; Labrousse, François; et al.
Abstract Finding new prognostic factors to identify patients with Hodgkin lymphoma (HL) at risk of treatment resistance or relapse remains challenging in daily practice. We evaluated the relationship between CD68 expression, interim positron emission tomography (iPET) results and outcome in 158 patients with HL diagnosed from February 1995 to July 2011. Immunohistochemistry (anti-CD68) gave two groups: low with ≤ 25% positive cells (121 patients) and high with > 25% (37 patients). Five-year overall survival was higher in the low group (88.4% vs. 63.2%, p = 0.0151), as was progression-free survival (74.5% vs. 40.7%, p = 0.0003). In 68 patients evaluable, iPET correlated with CD68: 13/52 patients (25%) in the low group had positive iPET as compared to 11/16 patients (68%) in the high group (p = 0.0016). This study confirms the prognostic value of CD68 in HL. We found a correlation between CD68 and iPET suggesting potential for a better stratification.